Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the value of [tex]\((f - g)(2)\)[/tex] when [tex]\(f(x) = 3x^2 + 1\)[/tex] and [tex]\(g(x) = 1 - x\)[/tex], let's go through it step-by-step.
1. Evaluate [tex]\(f(2)\)[/tex]:
Given [tex]\(f(x) = 3x^2 + 1\)[/tex],
[tex]\[ f(2) = 3(2)^2 + 1 = 3 \cdot 4 + 1 = 12 + 1 = 13. \][/tex]
2. Evaluate [tex]\(g(2)\)[/tex]:
Given [tex]\(g(x) = 1 - x\)[/tex],
[tex]\[ g(2) = 1 - 2 = -1. \][/tex]
3. Calculate [tex]\((f - g)(2)\)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2). \][/tex]
Substitute the values found:
[tex]\[ (f - g)(2) = 13 - (-1) = 13 + 1 = 14. \][/tex]
Hence, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
1. Evaluate [tex]\(f(2)\)[/tex]:
Given [tex]\(f(x) = 3x^2 + 1\)[/tex],
[tex]\[ f(2) = 3(2)^2 + 1 = 3 \cdot 4 + 1 = 12 + 1 = 13. \][/tex]
2. Evaluate [tex]\(g(2)\)[/tex]:
Given [tex]\(g(x) = 1 - x\)[/tex],
[tex]\[ g(2) = 1 - 2 = -1. \][/tex]
3. Calculate [tex]\((f - g)(2)\)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2). \][/tex]
Substitute the values found:
[tex]\[ (f - g)(2) = 13 - (-1) = 13 + 1 = 14. \][/tex]
Hence, the value of [tex]\((f - g)(2)\)[/tex] is [tex]\(\boxed{14}\)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.